Stokes flow past a composite porous spherical shell with a solid core (Archives of Mechanics - Test, 1996)
A general solution of the Brinkman equations in the form of an infinite series is presented. A representation for the solution of Brinkman's equations is also proposed and its equivalence to the infinite series is established. The usefulness of the representation is demonstrated by applying it to design a general method of solving an arbitrary Stokes flow past a composite porous spherical shell with a rigid core. Some physical properties, such as the drag and torque exerted on the composite sphere are calculated. Several illustrative examples are discussed.